Evidence of 2D anti-ferromagnetic ordering in rare-earth Langmuir–Blodgett films. (11th September 2019) - Singh, Arnab; Mukhopadhyay, Mrinmay K; Sanyal, Milan K; Stenning, Gavin; Langridge, Sean
Abstract: In recent years the ordering of spins in two-dimensions has received considerable attention due to both the fundamental physics interest and for the possible technological applications. Langmuir–Blodgett (LB) films with magnetic ions are ideal systems to study two-dimensional (2D) magnetic ordering as the distances of the magnetic-ions along the out-of-plane and in-plane directions differ by almost an order of magnitude and the effect of the substrate can be neglected. In particular, vortex formation in ferro and antiferro 2D magnetic structures are of current interest and LB films are ideal to study this evolving physics. We show here that 2D magnetic ordering along the in-plane direction of multilayered LB films changes from ferromagnetic to anti-ferromagnetic as the rare-earth magnetic ion is changed from Gadolinium (Gd) to Holmium (Ho). The in-plane magnetization results have shown that Gd based LB films exhibit a temperature dependent saturation moment due to the existence of a vortex structure. The results of the magnetization study presented here show that the Ho based LB films exhibit an in-plane anti-ferromagnetic ordering and the saturation moment is found to be almost independent of temperature indicating the absence of spin vortex structures. From a 1/ χ − T plot the asymtotic Curie point θ a and the Neel temperature θ N of the Ho-St LB film were found to be 66 K and 42 K respectively.